Virtual laboratory for simulation and modeling systems in engineering degree: A sustainable approach - Bolea, Yolanda; Grau, Antoni (2010 4th IEEE International Conference on E-Learning in Industrial Electronics, 2010)
In this paper we discuss about the use of computer simulations for sustainable systems. Specifically, we propose laboratory practices for Automatic Control subjects where the plants are sustainable systems. The interest is the simulation of this kind of systems to forecast their behavior in order to control and actuate over them. In this paper, the use of a didactic material for laboratory practices is explained. This pedagogical resource is published in a web (http://model.upc.edu) where the student can find the practice statements, the explanations and the software to develop sustainable models in form of laboratory practices for the subjects related with simulation and modeling in different engineering degrees, because we have the belief that undergraduate students must receive an Education for the Sustainability independently of their career without to avoid learning the basic and specifically concepts of the own subject.